“A Pharmaceutical and Therapeutical Review of Sneha Kalpana” - Sharma, Swati; Sharma, Manoj (International Research Journal of Ayurveda & Yoga, 2021)
Sneha Kalpana is a type of Aushadha Kalpana in which Sneha Paka(Taila Paka Or Ghrita Paka) is done with prescribed Kalka Dravya, Drava Dravya And Kwatha Dravya. It is the only kalpana which can be used through all the four routs of drug administration. i.e. Pana , Abhyanga, Nasya And Basti. Our acharyas has mentioned the use of medicated ghrita and taila in maximum diseases, except Urustambha. They specifically indicated their use in case of Vata Vyadhi. Demand of different types of medicated Taila And Ghrita is increasing in the market. Various pharmaceutical companies are preparing a numerous medicated taila and ghrita and claiming very good results. For preparing Taila Kalpana Or Ghrita Kalpana, firstly Taila And Ghrita are supposed to undergo the process called murchana sanskara. By doing Murchana Sanskara Dosha like Daurgandhatva, Ama etc. are removed and therapeutic potency of sneha increases. There are mainly three types of sneha paka mentioned in our classical texts: Mridu Paka, Madhayama Paka And Khara Paka according to their therapeutic use. So, this article presents a detailed description of Sneha Kalpana.